Role of Orbital Ultrasound in the Monitoring of Children with Raised Intracranial Pressure—Prospective Observational Study Conducted in Tertiary Care Centre - Selvam, Nithiya; Parameswaran, Narayanan; Ananthakrishnan, Ramesh (Journal of Pediatric Intensive Care, 2023)
Our objective was to evaluate the role of optic nerve sheath diameter measurement by orbital ultrasound in monitoring children with nontraumatic coma and increased intracranial pressure (ICP). A single-center prospective observational study was conducted in the pediatric intensive care unit (PICU) of a tertiary care teaching hospital in Puducherry, India. Children admitted to the PICU with features of raised ICP were enrolled. Baseline characteristics and raised ICP characteristics were recorded. Optic nerve sheath diameter (ONSD) measurements were taken in all children in the supine position using bedside ultrasound with a 12 MHz linear probe. The probe was initially placed in the axial plane, and measurements were taken at a distance of 3 mm posterior to the site at which the optic nerve enters the globe. Measurements were recorded sequentially 8th hourly till ICP features got resolved or the patient died. Along with each measurement, clinical parameters were recorded. The ONSD measurements were compared with clinical features. We also recruited children admitted to the PICU for other conditions without features of raised ICP as controls. We compared ONSD measurements of cases with controls. In total, 185 children were recruited, of which 81 had features of raised ICP and 104 were without increased ICP. The ONSD measurements in children with raised ICP were significantly higher as compared with those without ICP. Among children with raised ICP, there was a negative correlation between ONSD and Glasgow Coma Scale scores (r = −0.739, p ≤ 0.0001). In children with raised ICP, there was a significant difference in ONSD at different intervals, demonstrating a falling trend from admission to 32nd-hour readings. ONSD measurements were higher in children with clinical signs of increased ICP compared with controls, thereby suggesting that this noninvasive measure may be helpful in the neuromonitoring of children with neurologic insults.
Keywords: Optic nerve sheath diameter; raised intracranial pressure; nontraumatic coma; PICU